OBSERVATION OF THE PRINCIPLE OF EQUALITY OF ALL BEFORE LAW IN THE CONTEXT OF LEGAL RESPONSIBILITY OF A CITIZEN AND A STATE IN UKRAINE - Задорожня, Г. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article investigates the problem of "mutual" responsibility of a citizen and the state. The author states that the institution of state responsibility to a citizen functions in Ukraine on a legal principle, but such an important institution should find a clear normative constitution at the constitutional level.